An introduction to two-dimensional discrete dynamical systems: Una introducción a los sistemas dinámicos discretos bidimensionales - Santiago Santos, Alicia (2026)
A dynamical system can be informally defined as a system whose state is uniquely specified by a set of variables and whose behavior is described by predefined rules. The objective of this article is to present the reader with an introduction to certain types of mathematical models (also known as dynamical systems). In particular, to study one-dimensional and two-dimensional discrete models. Finally, some examples and their solutions are given.